Influence of Relief and Land Cover on the Distribution of Values of the Land Surface Temperature in Upper Parsęta River Area - Kubiak, Marta; Stach, Alfred (Quaestiones Geographicae, 2013)
The primary research problem presented in the article is verification of the thesis on the influence of relief and land cover type on the spatial variability of the land surface temperature (LST) distribution in the area including the river catchment area of upper Parsęta. The paper presents the use of thermal channels from two Landsat ETM+ scenes pictures, Corine Land Cover database from 2000 as well as the DTED-2 digital elevation model. Two ETM+ thermal bands processing algorithms were used for calculation of the land surface temperature: Qin et al. (2001) and Jiménez-Muňoz et al. (2003). Conducted statistical tests show significant differences of the land surface temperature values between particular land cover forms as well as types of relief. LST maps can be applied in topoclimatology eg. to detail and verify the in situ measurements.